A study on some physical and chemical properties of Kurk Stream discharging into Lake Hazar - Sen, Bulent; Golbasi, Selami (Ege Univ, Fac Fisheries, 2008)
In this study, physical and chemical properties of Kurk Stream discharging into Lake Hazar were investigated between December 2004 and November 2005. For this purpose, water samples were collected at monthly intervals from five stations chosen on Kurk Stream. The values and degrees of flowing rate, temperature, electrical conductivity, turbidity, pH, dissolved oxygen, total hardness, total alkalinity and chloride were determined for each station separately. The results of analysis showed that Kurk Stream is slightly alkaline. According to Water Quality Criteria for Inland Water Resources, Kurk Stream can be classified as class II (less polluted water) with respect to chloride concentrations and class I (high quality water) in terms of other parameters examined. Physical and chemical properties of Kurk Stream varied according to geomorphology and morphometric properties of stream bed besides velocity and volume of water which change with seasons. Stream carries a total of 11.435.040 m(3) year(-1) water into Lake Hazar.
Keywords: Kurk Stream; Hazar Lake; Water Quality; Running Water; Limnology